2015
DOI: 10.4103/0253-7176.168586
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Effect of Atypical Antipsychotics on Speech

Abstract: Background:Most of the studies have looked into the effect of typical antipsychotics on speech secondary to tardive dyskinesia.Aims:This study was aimed to explore the factors predicting the effect of atypical antipsychotic medications on the production of speech.Materials and Methods:One hundred and forty patients on stable regimen of three or more months on risperidone (92), olanzapine (28), aripiprazole (14), and clozapine (6) were recruited for the study. Speech was assessed by maximum phonation duration t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Indeed, some have suggested that antipsychotic medication improves communication since it is associated with reduced incoherence and tangentiality 53 . However, there is also some evidence that antipsychotics reduce intelligibility of speech and induce poverty of speech 20,21 . Antipsychotics can also cause acute laryngeal dystonia 54 or laryngeal dyskinesia 55 , causing stridor and thereby negatively impacting speech.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, some have suggested that antipsychotic medication improves communication since it is associated with reduced incoherence and tangentiality 53 . However, there is also some evidence that antipsychotics reduce intelligibility of speech and induce poverty of speech 20,21 . Antipsychotics can also cause acute laryngeal dystonia 54 or laryngeal dyskinesia 55 , causing stridor and thereby negatively impacting speech.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the remedying effects of antipsychotic medication on language disturbances. Importantly, there is reason to assume that antipsychotic drugs may contribute to some of these language perturbations 20,21 . Specifically, antipsychotic drugs' effects on dopamine receptors can be hypothesized to impair language, in several ways.…”
Section: Introductionmentioning
confidence: 99%
“…It has been related to the duration of antipsychotic treatment and extrapyramidal side effects including dopaminergic supersensitive states such as tardive dyskinesia and dystonia. [6] Clozapine, with its lower dopaminergic affinity, is less likely to be involved in extrapyramidal side effects-related pathogenesis. Apart from dopamine, multiple neurotransmitter systems, including muscarinic and α-adrenergic receptors, where clozapine exerts its influence have also been implicated.…”
Section: Discussionmentioning
confidence: 99%
“…[5] There is literature on iatrogenic causation with antidepressants and antipsychotics such as risperidone and aripiprazole. [6] Although rarely, clozapine has also been reported to cause stuttering. A retrospective study in Ireland estimated the prevalence of stuttering as 0.92% (6 of 654) in patients treated with clozapine.…”
Section: Discussionmentioning
confidence: 99%
“…Antipsychotic medications have the ability to disrupt speech processing mechanisms because they affect the neuromuscular system. Speech problems, particularly acquired types, can affect communication and life experiences [4].…”
Section: Introductionmentioning
confidence: 99%